КОМБИНИРОВАННЫЕ ПРЕПАРАТЫ В ТЕРАПИИ ОСТРЫХ РЕСПИРАТОРНЫХ ВИРУСНЫХ ИНФЕКЦИЙ: ОЦЕНКА КЛИНИКО- ЭКОНОМИЧЕСКОЙ ЭФФЕКТИВНОСТИ - А. А. Зайцев; О. И. Клочков (SINAPS LLC, 2015)
The publication is dedicated to the analysis of clinical and cost effectiveness of the combination of drugs for the symptomatic treatment of acute respiratory viral infections. The presented results demonstrate a higher clinical and economic feasibility of treatment of acute respiratory viral infections using the drug Inflyunet® compared with alternative treatment. The use of combined drugs assosiated with less adverse effects than the use of "set" monocomponent preparations for the treatment of acute respiratory viral infections and it is economically more cost-effective for the patient.